EFFECT OF MINDFULNESS-BASED GROUP COUNSELING ON ANXIETY IN INFERTILE WOMEN UNDERGOING IN VITRO FERTILIZATION TREATMENT IN HAMEDAN, IRAN - Kalhori, Fatemeh; Masoumi, Seyedeh Zahra; Mohagheghi, Hossein; Parsa, Parisa; Mohammadi, Younes (Journal of Postgraduate Medical Institute, 2020)
Objective: To determine the effect of mindfulness-based group counseling on anxiety in infertile women undergoing in vitro fertilization (IVF). Methodology: This randomized controlled trial was performed on 90 infertile women who underwent IVF in the infertility center of Fatemieh Hospital Hamadan in 2016. The participants were randomly divided into two groups; case and control. After the initial completion of the Spielberger demographic and anxiety questionnaire by both groups, 8 group counseling sessions with the subject of mindfulness were held in the intervention group for 90 minutes a day and twice a week. The counseling axes included: auto-guidance, barriers, breathing with mindfulness, staying in the moment, accepting and permission to attend, non-truthful thoughts and how to do self-care. Then the Spielberger anxiety questionnaire was completed by both groups after intervention. The data were analyzed using SPSS version 21. Results: There was a significant difference between the control and the intervention groups in terms of apparent anxiety (p <0.001) and the hidden anxiety (p <0.001) before and after the intervention. Moreover, after the intervention, the means of apparent and hidden anxiety were lower in the case group than the control group (p <0.001). Conclusion: The mindfulness-based group counseling was found to reduce the apparent and hidden anxiety of infertile women undergoing IVF.